Reverse Logistics Operations in Singapore to Support Asia Pacific Regions - Tan, A.W.K.; Hosie, Peter (Inderscience Enterprises Limited, 2010)
This paper describes an empirical study of companies based in Singapore who use reverse logistics operations to support their Asia Pacific market. Findings from this study increase the understanding of the various reverse logistics practices used to sustain key industries operations in the Asia Pacific region. An analysis was undertaken of various methods used when managing reverse logistics operations. Some general practices and barriers were identified in the data that led to important findings relating to reverse logistics planning and operations in Asia, including attempts to recapture the value of returned products. Most product returns are deemed obsolete by virtue of being at the end of their product lifecycle with no possibility of being recycled, reused or resold. Channel partners (i.e., distributors and retailers) made most disposal decisions, as most of the respondents do not deal directly with end consumers. Some respondents did not measure their performance with respect to reverse logistics. The key barriers to reverse logistics were identified as competition, financial constraint or lack of environmental regulations.